SEQUENTIAL EXTRACTION OF SELECTED HEAVY METALS IN THE SOILS OF ABUJA, NIGERIA - Ibrahim, Rabiu; Dauda, M. S.; Igwemmar, N. C.; Abdu, B. (FUDMA Journal of Sciences, 2024)
Speciation of selected heavy metals in Abuja metropolitan soil samples was investigated using a sequential extraction analytical technique. Flame atomic absorption spectrometer was used for instrumental analysis. Metals were bound in six operational phases, in the sequential extraction method. Pb, Mn and Cd speciate more in exchangeable,  As and Ni speciate more in bound to carbonate, Cu and Fe speciate more in bound to Fe-Mn oxide,  Cr and Zn  speciate more in organically bound  while Al speciate more in residual in urban soil samples. In sub-urban samples, Pb and Cd  speciate more in exchangeable and bound to Fe-Mn oxide, Cu speciate more in exchangeable, Al speciate more in bound to Fe-Mn oxide, Fe and Al speciate more in residual, Ni and As speciate more in bound to carbonate, Zn speciate more in organically bound and  Cr speciate more in exchangeable and organically bound.  Asokoro Forest (control) has most of the metals as non-residuals except Al and As which speciate more in residual phase. Sequence of ionic mobility in decreasing order for Abuja urban soils is as follows: Zn>Cu>Fe>Al>Mn>>As>Ni>Cr>Cd>Pb and in sub-urban soil samples is: Zn>Cu>Fe>Al>Mn>>Ni>As>Pb>Cd>Cr. From the results, it can be deduced that Zn is the ion with highest speciation. This portends danger to Abuja metropolis due to Zn phytoxicity which hinders photosynthesis in plants, thereby increasing the amount of CO2 giving rise to global warming. This requires that relevant authorities should enforce reduction of the activities that lead to abundance of Zn in Abuja soils.
Keywords: Abuja; Speciation; Sequential extraction; Mobility; Global Warming